Incidental detection of late presenting co-arctation of the aorta on chest x-ray: the importance of rib notching. (27th January 2012) - Warne, Richard Roger; Ong, Jeremy Sze Luong; Murray, Conor P
Abstract : A 31-year-old obese male presented to the emergency department with symptoms and signs suggestive of a viral upper respiratory tract illness with a background of low exercise tolerance. Rib notching was identified on plain film chest radiography and subsequent CT of the thorax identified a moderately tight 2-mm juxta-ductal co-arctation of the aorta with multiple enlarged chest wall collaterals. The patient underwent a two-stage percutaneous procedure involving stent insertion and angioplasty up to 16 mm with significant improvement in exercise capacity and a modest reduction in blood pressure.